Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Squares difference

  1. Jun 20, 2013 #1
    Hello, how can I prove using factorization that a^2 - b^2 = (a+b)(a-b) ?

    a*a - b*b I should get something like a(a-b)+b(a-b) but how ?

    thanks
     
  2. jcsd
  3. Jun 20, 2013 #2
    a2 - b2 == a2 - b2 + ab - ab == a2 + ab - b2 - ab == a(a+b) - b(a+b) == ?
     
  4. Jun 20, 2013 #3
    Ok but how do I get a^2 - b^2 + ab - ab from a^2 - b^2 ?
     
  5. Jun 20, 2013 #4

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    Add ab and subtract ab.
     
  6. Jun 20, 2013 #5

    Mark44

    Staff: Mentor

    You can always add zero to any expression (here in the form of ab + (-ab), and you can always multiply an expression by 1.
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook